A photochromic carbazolyl-imidazolyl radical complex. Issue 32 (1st April 2022) - Kawanishi, Yasuki; Segawa, Yasutomo; Mutoh, Katsuya; Abe, Jiro; Kobayashi, Yoichi
Abstract : A carbazole-incorporated photochromic radical complex is synthesized. Abstract : A carbazole-incorporated photochromic radical complex is synthesized. The long-wavelength photosensitivity of the photochromic reaction of the molecule is enhanced up to ∼580 nm by substituting a triphenylamine group into the 3-position of the carbazole moiety. These photochromic reactions are investigated by subpicosecond-to-microsecond transient absorption measurements.